IDENTIFIKASI HUKUM ADAT (PERSPEKTIF BAHAGIAN KAJIAN SOSIOLOGI HUKUM) - Zulherman Idris; Miftahur Rachman (JOURNAL EQUITABLE, 2021)
This paper focuses on various studies regarding the identification of customary law which consists of several views, the views of western scholars and Indonesian scholars. The research method used is socio-legal. The results of the discussion obtained from western scholars are based on the ideas argued by Snouch Hurgronje, van Vollenhoven and Ter Haar. Meanwhile, Indonesian scholars regarding the identification of customary law are taken from the arguments of R. Soepomo and Moh. Koesno